Comprehension Profile of Patient Education Materials in Endocrine Care - Singh, Som; Qureshi, Fahad; Borthwick, Kiera; Singh, Sagar; Menon, Shreya; Barthel, Brandon (Kansas Journal of Medicine, 2022)
Introduction. The internet is an ever-evolving resource to improve healthcare literacy among patients. The nature of the internet can make it difficult to condense educational materials in a manner applicable to a worldwide patient audience. Within the realm of endocrinology, there is a lack of a comprehensive analysis regarding these pathologies in addition to educational materials related to their medical workup and management. The aim of this study is to assess contemporary online patient education material in endocrinology and management of care. Methods. Analysis of the readability of 1500 unique online education materials was performed utilizing 7 readability measures: Flesch Reading Ease (FRE), Flesch-Kincaid Grade Level (FKGL), Gunning Fog Index Readability Formula (FOG), Simple Measure of Gobbledygook Index (SMOG), Coleman-Liau Index (CLI), automated readability index (ARI), and Linsear Write Formula (LWF). Results. The average grade level readability scores from 6 measures (FKGL, FOG, SMOG, CLI, ARI, LWF) was ≥11 which corresponds to a reading level at or above the 11th grade. The average FRE between adrenal, diabetes and thyroid-related education material ranged between “fairly difficult” to “very difficult”. Conclusions. The current readability of contemporary online endocrine education material does not meet current readability recommendations for appropriate comprehension of the general audience.